IMPACT OF DIGITAL FACTORY TOOLS ON DESIGNING OF WAREHOUSES - Buckova, Monika; Krajcovic, Martin; Jerman, Boris (Journal of Applied Engineering Science, 2017)
In this article the basic information for cost reduction in warehouse facilities by use of new technologies is presented. The core of article constitutes of the description of new technologies and their impact on design warehouses. The article discusses the influence of new technology on the way the data is collected, on the storage of goods, their processing and on the sequences of delivery of goods to customers in the requested format and quality.